(untitled) (Research, Society and Development, 2022)
The new pedagogical practices require the emergence of profound changes, as the educational process must not be reduced to learning, and its dimensions of coexistence and socialization must not be ignored. The school needs the courage of Metamorphosis, the urgency of changes to guarantee transformations that dialogue with complexity and transdisciplinary, as well as synchronization with the realities experienced by teachers. The present article has as its study problem the need to design new pedagogical practices, in teacher training and knowledge. The research is of the action research type, carried out with professors from the strictu sensu, from the doctorate in education. The objective of the study was to demonstrate the urgency of transformation and the need for new practices based on complexity, transdisciplinary and transformative education, and that subsidize teacher training within a new Ecosystem Paradigm. Cooperation and eco-training are recognized as one of the keys to this process, with dialogue being the greatest instrument for this mediation. We believe in the future of the pedagogy of encounter, of reciprocity, dedicated to teacher training. It is concluded that this educational multidimensionality contemplates an ecosystem paradigm that requires the creation of conditions so that students can discover the complexity of their human condition, learning to welcome diversity, have an ecological conscience, solidarity and social responsibility.